Heterogeneity in Spatiotemporal Variability of High Mountain Asia's Runoff and Its Underlying Mechanisms - Yanxin Zhu; Yan‐Fang Sang; Bin Wang; Arthur Lutz; Shi Hu; Deliang Chen; Vijay P. Singh (Water resources research, 2023)
Abstract High Mountain Asia (HMA) is the headwater area for major Asian rivers, providing a vast amount of freshwater to billions of people in Asia. These rivers also make their surrounding areas highly vulnerable to destructive water‐related disasters. However, the complex spatiotemporal variability of runoff over HMA and its underlying mechanisms are poorly understood. This study investigates into the spatial heterogeneity of HMA's runoff variability at three timescales (interannual, interdecadal, and multidecadal) and the roles played by climate conditions and catchment properties. We find significant interannual and multidecadal variability of runoff in west and central HMA, and significant interdecadal variability in central and east HMA. At interannual and multidecadal timescales, the runoff variability tends to be more significant in dryer basins. The variability of runoff at the three timescales is largely controlled by climate variations, especially precipitation. The catchment properties, including groundwater storage and glacier‐snow meltwater, also play important roles in regulating the effect of precipitation. In particular, the high contributions of glacier‐snow meltwater in east HMA can weaken the response of runoff variability to precipitation at interannual and multidecadal timescales. The space‐time patterns of runoff variability over HMA are driven by atmospheric drivers including El Niño‐Southern Oscillation, Interdecadal Pacific Oscillation, and Atlantic Multidecadal Oscillation across timescales. The results of this study provide a better understanding of HMA's runoff variability and its physical mechanisms, which have critical implications for sustainable freshwater management and effective risk mitigation in this densely populated and ecologically vulnerable region.